A girl named Disaster - Farmer, Nancy 1941- (New York Puffin Books, 1998)
While fleeing from Mozambique to Zimbabwe to escape an unwanted marriage, Nhamo, an eleven-year-old Shona girl, struggles to escape drowning and starvation and in so doing comes close to the luminous world of the African spirits.
Keywords: Shona (African people) -- Juvenile fiction; Shona (African people) -- Fiction; Survival -- Fiction; Supernatural -- Fiction; Mozambique -- Fiction; Zimbabwe -- Fiction; Africa -- Fiction